STUDENT’S IDENTITIES IN SCHOOL LITERACY MOVEMENT: TOWARD A DISCURSIVE PERSPECTIVE FOR LITERACY EDUCATION IN INDONESIA - Deris Nurjamiliatul Afifah; Fuad Abdullah; Arini Nurul Hidayati; Agis Andriani (JALL (Journal of Applied Linguistics and Literacy), 2021)
The School Literacy Movement (hereafter, SLM) has become a predominant investigative issue recently. This program supports students (e.g. secondary school students) to cultivate their literacies and enables them to invigorate their reading habits. However, empirical attempts accentuating types of the student’s identities represented in the School Literacy Movement remains under-explored. Thus, this study aimed at filling the void. The data were collected from a student’s reflective journals outlining her experiences amid participating in SLM. Technically, the data were analyzed discursively through Socio-Semantic Inventory Analysis (van Leuween, 1996). The findings designated that types of the student’s identities represented in School Literacy Movement encompass an observing student, an idealistic student, a self-restraint student, an active reader, a melancholic student, and a technology-oriented student. Pedagogically, this study suggests that SLM should not only be viewed as an auxiliary program fostering students’ literacies but also a bridge connecting students to possess learning awareness and autonomy in English language learning.